Radiographic study of developmental alteration in tooth number among children in Kuantan - Sukmasari, Susi; Ardini, Yunita Dewi; Azaldin, Nurul Hazirah; Ismail, Nabilahuda (Kulliyyah of Detistry - IIUM, 2013)
Objectives: The aim of this research was to determine the prevalence, distribution and association of developmental alteration in tooth number with gender, location, and presence of delayed eruption of tooth among children who attended to polyclinic dental student of International Islamic University Malaysia (IIUM). Materials and methods: A cross sectional study on total 727 Orthopanthomograms (OPGs) of 3-17 years old children who attended to Students’ polyclinic, from April 2009 to July 2012. OPGs with presence of hyperdontia and hypodontia were scrutinized to find out the prevalence, distribution and association. The data was analyzed comparing gender, location and presence of delayed eruption. The differences between the groups were tested using Chi-square test, with p < 0.05. All data was analyzed using SPSS version 20. Results: Out of 727 OPGs, 71 OPGs showed developmental alteration in tooth number. The prevalence of developmental alteration in tooth number was 98/1000 OPGs within 3 years. Prevalence of hyperdontia was 18/1000, hypodontia 78/1000 and both 1/1000. Among those 71 OPGs, the gender differences were: males (49.3%) and females (50.7%). Locations of alteration were found in maxilla (45.1%), mandible (40.8%) and both (14%). The finding of presence delayed eruption was (7%). There was significant differences between alteration in tooth number with location as (p<0.05) while there were no significant differences between alteration in tooth number with gender and delayed eruption as (p>0.05). Conclusions: This study showed that hyperdontia was considerably lower, while hypodontia was higher compared to the previous study that was done in Malaysia. There was association between alteration in tooth number with location and no association between alteration in tooth number with gender and delayed eruption. In addition, early identification of developmental alteration in tooth number is useful to avoid complications and to assure successful management.